2021
DOI: 10.3390/s21051733
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Hand Gesture Recognition Utilizing Electroencephalogram as Input to the Machine Learning and Network Neuroscience Algorithms

Abstract: Surgical gestures detection can provide targeted, automated surgical skill assessment and feedback during surgical training for robot-assisted surgery (RAS). Several sources including surgical videos, robot tool kinematics, and an electromyogram (EMG) have been proposed to reach this goal. We aimed to extract features from electroencephalogram (EEG) data and use them in machine learning algorithms to classify robot-assisted surgical gestures. EEG was collected from five RAS surgeons with varying experience whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Several prospective studies ( 22 24 ) have investigated the prediction of PODs in patients undergoing cardiovascular surgeries using a substantial array of preoperative clinical parameters. These studies reported an area under the curve (AUC) values ranging from 0.74 to 0.83, which were marginally lower than the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies ( 22 24 ) have investigated the prediction of PODs in patients undergoing cardiovascular surgeries using a substantial array of preoperative clinical parameters. These studies reported an area under the curve (AUC) values ranging from 0.74 to 0.83, which were marginally lower than the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson filter is the simplest form of ranking that is performed by computing the correlation of every pair of features for all features [47]. ANOVA calculates the parametric statistical hypothesis score, F-value by comparing two or more samples of data (typically three samples) [48]. Chi-square scores calculate the dependencies between features by calculating the error between the observed and expected values [49].…”
Section: First Layer Feature Selectionmentioning
confidence: 99%